Proton-coupled electron transfer promotes the reduction of ferrylmyoglobin by uric acid under physiological conditions. Issue 29 (23rd March 2017) - Zawadzki, Andressa de; Cardoso, Daniel R.; Skibsted, Leif H.
Abstract : Uric acid prevents the oxidative toxic effects of ferrylmyoglobin during red meat digestion. Abstract : The hypervalent muscle pigment ferrylmyoglobin, MbFe(iv ){O, is not reduced by urate monoanions at physiological conditions despite a strong driving force of around −30 kJ mol −1 while for low pH, uric acid was found to reduce protonated ferrylmyoglobin, MbFe(iv ){O, H +, efficiently in a bimolecular reaction with k 1 = 1.1 ± 0.1 × 10 3 L mol −1 s −1, Δ H ‡ = 66.1 ± 0.1 kJ mol −1 and Δ S ‡ = 35.2 ± 0.2 J mol −1 K −1 . For intermediate pH, like for anaerobic muscles and for meat, proton-coupled electron transfer occurs in a transition state, MbFe(iv ){O⋯H + ⋯urate ‡, which is concluded to be formed from uric acid and MbFe(iv ){O rather than from urate and MbFe(iv ){O, H + with k 3 = 9.7 ± 0.6 × 10 2 L mol −1 s −1, Δ H ‡ = 59.2 ± 0.1 kJ mol −1 and Δ S ‡ = 11.5 ± 0.3 J mol −1 K −1 . The activation parameters as calculated from the temperature dependence of the pH-reduction profile in aqueous 0.067 mol L −1 NaCl (from 25 °C up to 40 °C), support a mechanism for reduction of hypervalent heme iron, where initial proton transfer to oxo-iron initiates the intermolecular electron transfer from urate to ferrylmyoglobin. The concentration of the powerful prooxidant ferrylmyoglobin increases strongly during digestion of red meat in the stomach. A concomitant increase in uric acid concentration may serve as an inherent protection against radical formation by ferrylmyoglobin.